Manik Buangsi - Almario, Virgilio S.; Ibarra Cruz Crisostomo;Leonardo Giron (Quezon City, Philippines : Adarna House Inc., 2005)
From the Samals in the Southern Philippines comes this story of undying love between a mortal and an immortal.
Keywords: CHILDREN'S LITERATURE -- PHILIPPINES